New fluorous ponytailed 4‐[(2, 2, 2‐trifluoroethoxy)methyl]pyridinium halide salts. Issue 12 (5th December 2016) - Lu, Norman; Alagesan, Mani; Ho, Chi-Liang; Wei, Rong-Jyun; Kung, Chih-Chieh; Chang, Jung-Shan; Wen, Yuh-Sheng; Liu, Ling-Kang
Abstract : The reaction of 4‐[(2, 2, 2‐trifluoroethoxy)methyl]pyridine with H X ( X = I or Cl) yielded new fluorous ponytailed pyridinium halide salts exhibiting two types of hydrogen bonds, namely N—H… X and C—H… X . In the IR spectra, the iodide salt exhibited a blue shift with respect to the pyridinium N—H stretching band compared to the chloride salt. Abstract : It is possible that fluorous compounds could be utilized as directing forces in crystal engineering for applications in materials chemistry or catalysis. Although numerous fluorous compounds have been used for various applications, their structures in the solid state remains a lively matter for debate. The reaction of 4‐[(2, 2, 2‐trifluoroethoxy)methyl]pyridine with H X ( X = I or Cl) yielded new fluorous ponytailed pyridinium halide salts, namely 4‐[(2, 2, 2‐trifluoroethoxy)methyl]pyridinium iodide, C8 H9 F3 NO + ·I −, (1), and 4‐[(2, 2, 2‐trifluoroethoxy)methyl]pyridinium chloride, C8 H9 F3 NO + ·Cl −, (2), which were characterized by IR spectroscopy, multinuclei ( 1 H, 13 C and 19 F) NMR spectroscopy and single‐crystal X‐ray diffraction. Structure analysis showed that there are two types of hydrogen bonds, namely N—H… X and C—H… X . The iodide anion in salt (1) is hydrogen bonded to three 4‐[(2, 2, 2‐trifluoroethoxy)methyl]pyridinium cations in the crystal packing, while the chloride ion in salt (2) is involved in six hydrogen bonds to five 4‐[(2, 2, 2‐trifluoroethoxy)methyl]pyridinium cations, which is attributed to the smaller size and reduced polarizability of the chloride ion compared to the iodide ion. In the IR spectra, the pyridinium N—H stretching band for salt (1) exhibited a blue shift compared with that of salt (2).